Gastric Mallory-Weiss tear after cardiopulmonary resuscitation: a case report - Rami Esmat; Mohamed-Naguib Wifi; Abeer A Abdellatif; Mohamed Alboraie (Wolters Kluwer Medknow Publications, 2021)
Abstract Mallory-Weiss tear is a rare complication that could result following cardiopulmonary resuscitation, leading to vigorous upper gastrointestinal bleeding. We illustrate a case of an 84-year-old male patient, admitted to the hospital for investigation of lung nodules and bilateral pleural effusion. The patient developed cardiac arrest during pleural aspiration, and cardiopulmonary resuscitation was done, which was followed shortly by an attack of acute upper gastrointestinal bleeding. Urgent upper endoscopy revealed a mucosal tear with submucosal oozing of blood and two large vessels in its floor, which were successfully managed endoscopically with both injection and hemoclips. This case report emphasizes the importance of considering this potential complication, especially after performing a successful cardiac resuscitation.